2021
DOI: 10.3389/fcell.2021.673839
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights and Current Evidence for Mechanisms of Atherosclerosis: Mitochondrial Dynamics as a Potential Therapeutic Target

Abstract: Cardiovascular disease (CVD) is the main cause of death worldwide. Atherosclerosis is the underlying pathological basis of CVD. Mitochondrial homeostasis is maintained through the dynamic processes of fusion and fission. Mitochondria are involved in many cellular processes, such as steroid biosynthesis, calcium homeostasis, immune cell activation, redox signaling, apoptosis, and inflammation, among others. Under stress conditions, mitochondrial dynamics, mitochondrial cristae remodeling, and mitochondrial ROS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 198 publications
(210 reference statements)
1
27
0
Order By: Relevance
“…More importantly, the elimination of the so-called junk foods that are high in trans fatty acids (TFA), TG, LDL, and low in HDL can significantly improve patients' lipid profiles. On the other hand, an increased level of TFA additionally increases the amount of pro-inflammatory cytokines, causing endothelial dysfunction and insulin resistance [78]. Artificial TFAs are associated with an increased risk of atherosclerosis and cardiovascular events [79].…”
Section: Atherosclerosis and The Action Of Lycopenementioning
confidence: 99%
“…More importantly, the elimination of the so-called junk foods that are high in trans fatty acids (TFA), TG, LDL, and low in HDL can significantly improve patients' lipid profiles. On the other hand, an increased level of TFA additionally increases the amount of pro-inflammatory cytokines, causing endothelial dysfunction and insulin resistance [78]. Artificial TFAs are associated with an increased risk of atherosclerosis and cardiovascular events [79].…”
Section: Atherosclerosis and The Action Of Lycopenementioning
confidence: 99%
“…Mitochondrial shape affects the ability of cells to distribute their mitochondria to specific subcellular locations. Fusion and fission allow the mitochondrial exchange of lipid membranes and intramitochondrial content, which is crucial for maintaining the health of a mitochondrial population ( 51 ). For instance, MFN1 and MFN2 ablation in fibroblasts induce reduced respiratory capacity and great heterogeneity in mitochondrial shape and membrane potential ( 52 ).…”
Section: Regulation Of Mitochondrial Dynamicsmentioning
confidence: 99%
“…In recent years, a growing number of studies have shown that atherosclerosis may be related to mitochondrial fusion and fission. 64 In recent years, a growing number of studies have shown that atherosclerosis may be related to mitochondrial fusion and fission. 64 During the early stages of atherosclerosis, increased ROS levels induce endothelial dysfunction, vascular inflammation, and accelerated accumulation of oxidized low-density lipoprotein (ox-LDL) in the arterial wall.…”
Section: Role Of Mitochondrial Dysfunctionmentioning
confidence: 99%
“…64 In recent years, a growing number of studies have shown that atherosclerosis may be related to mitochondrial fusion and fission. 64 During the early stages of atherosclerosis, increased ROS levels induce endothelial dysfunction, vascular inflammation, and accelerated accumulation of oxidized low-density lipoprotein (ox-LDL) in the arterial wall. Excessive LDL deposition can induce apoptosis of vascular cells through a dependent mitochondrial pathway after oxidative modification.…”
Section: Role Of Mitochondrial Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation